Film and comic books - Gordon, Ian; Gordon, Ian; Jancovich, Mark; Jancovich, Mark; McAllister, Matthew P.; McAllister, Matthew P. (University Press of Mississippi, 2007)
Incompatible visual ontologies? : The problematic adaptation of drawn images / Pascal Lef(c)♭vre -- Dick Tracy: in pursuit of a comic book aesthetic / Michael Cohen -- Translation creativity and alien econ(c)omics: from Hollywood blockbuster to Dark Horse comic book / Kerry Gough -- Will the real wolverine please stand up?: Marvel's mutation from monthlies to movies / Derek Johnson -- When Gen-X met the X-Men: retextualizing comic book film reception / Neil Rae and Jonathan Gray -- "Wham! Bam! The X-Men are here": the British broadsheet press and the X-Men films and comic / Mel Gibson -- Unbreakable and the limits of transgression / Aldo J. Regalado -- Teen trajectories in Spider-Man and Ghost World / Martin Flanagan -- It's a bird! It's a plane! No, it's DVD!: Superman, Smallville, and the production (of) melodrama / Rayna Denison -- American Splendor: translating comic autobiography into drama-documentary / Craig Hight -- El Santo: The case of a Mexican multimedia hero / David Wilt -- From blockbuster to flop? the apparent failure (or possible transcendence) of Ralf K(c)œnig's queer comics aesthetic in Maybe ... maybe not and Killer condom / Paul M. Malone -- Old Malay heroes never die: the story of Hang Tuah in films and comics / Jan van der Putten and Timothy P. Barnard -- Enki Bilal's intermedial fantasies: from comic book Nikopol Trilogy to film Immortals (ad vitam) / Sophie Geoffroy-Menoux